Genetic Identification of Freshwater Fish Species Through DNA Barcoding from Lake Lebo Taliwang, West Nusa Tenggara - Tuty Arisuryanti; Rika Lathif Hasan; Khadija Lung Ayu; Nofita Ratman; Lukman Hakim (Universitas Gadjah Mada, 2019)
Lake Lebo Taliwang is one of the lakes in the West Nusa Tenggara with high freshwater fish species diversity. However, the species identification of freshwater fish species from Lake Lebo Taliwang using DNA barcoding is very limited. Therefore, the objective of this study was to identify seven samples of freshwater fish species collected from Lake Lebo Taliwang based on COI mitochondrial gene as a DNA barcoding marker and establish library COI sequences of Indonesian freshwater fish. We are using a standard DNA analysis and data obtained from this study was then examined using Nucleotide BLAST and the phylogenetic tree was analyzed using the Neighbour-Joining (NJ) method with Kimura 2 Parameter (K2P) model. The results revealed that among the seven samples of freshwater fishes collected from the Lake Lebo Taliwang, three samples were identified as Anabas testudineus, the other three samples were Barbodes binotatus and one sample was Trichopodus trichopterus. The level of similarity of these freshwater fish samples referred to the database from the GenBank and BOLD was between 98-100%. The NJ tree supports the clade of each species identified in this study. This occurrence indicated that DNA barcoding by using the COI mitochondrial gene was proven to be able to identify the freshwater fish samples accurately.